Reader Response To Racism In Harper Lee's Novel : ToKill A Mockingbird (1960) - Fitrisari, Marselina Nugraheni, Dr. M Thoyibi, M.S (2016)
This study is about racism in To Kill A Mockingbird (1960) by Harper Lee. It is analysed by using Reader Response approach that is proposed by Louise Rosenblatt. The objectives of this study are to know readers responses to racism on the GoodReads website. This research seizes on qualitative research. The primary data of this study is GoodReads website. The secondary data of this study is taken from literary books, websites, and the other sources that related to the issue of racism. There are four conclusions which can be drawn from this study. First, there is 18 issues reader responses on GoodReads. Second, the background of the readers are consist of the country, age, religion, race, and gender. Third, the reason reader disagree on racism, because based on readers reviews it is would be cause racism victim lost in their human right. In the other side it is would be damage some people included "negro" in every countries especially in America. Fourth, readers said that they are interested in racism issue because the racism issue on this novel is very visible to Tom Robinson which as long as in the court he was accused rape white-man despite he never did. Key words : Racism, To Kill A Mockingbird, Reader Response.